Terminal Condylar Facets of the Femur: Implications for Knee Arthroplasty - Athavale, Sunita; Kotgirwar, Sheetal; Deopujari, Rashmi; Sinha, Urmila; Trivedi, Soumitra; Lalwani, Rekha (The Journal of Knee Surgery, 2018)
In wake of changing lifestyle and increasing surgical expertise, knee replacement surgeries have become common. Attempts at improving the postoperative range of motion have prompted high-flexion knee arthroplasties. Consequently, there is a need to study the anatomy of knee joint in high flexion. This study focused on a holistic description of terminal condylar articular facet (TCAF; part of the femoral articular area in contact with the tibia in high flexion) of medial and lateral condyles and their quantification. In total, 104 dry femora and 16 dissected cadaveric knee joints (10 adult and 6 fetal) were studied. In most cases, the medial TCAF showed a tongue- or wedge-shaped extension in its lateral half, which has been referred to as extended condylar facet (ECF). The surface area of the ECF was approximately 0.5 cm2. In adult cadaveric dissections, the fibrous capsule showed the lax attachment beyond the ECF, thus creating a cave in the medial tibiofemoral compartment. These features were absent in fetal dissection. The presence of an ECF has not been documented in dry bones and has not been quantified. The variability of the size of this extension supports the hypothesis of this being an acquired trait. This study is expected to provide factual data for implant design improvement and a new anthropological data on Indian femora.
Keywords: condyles; high-flexion knee arthroplasty; posterior horn; total knee arthroplasty